1999
DOI: 10.1111/j.1471-0528.1999.tb08433.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in births at and beyond term: evidence of a change?

Abstract: Objective To examine trends in the distribution of births at and beyond term in New South Wales and in particular, to determine whether any changes are associated with changes in the obstetric practices of induction and elective caesarean section. Design Cross‐sectional analytic study. Setting New South Wales, Australia. Population All 540,162 women delivering a singleton cephalic‐presenting infant of gestational age ≥ 37 weeks from 1 January 1990 to 31 December 1996. Methods Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…2,3 Systematically proposing induction is a long-standing policy in many countries, including France and Canada; 2,4 in 2004, the American College of Obstetricians and Gynecologists updated their guidelines to promote a policy of systematic induction more actively but recommended that women 'with unfavourable cervixes can undergo labour induction or be managed expectantly'. 5 Studies from Australia, Canada, and the USA report recent rates of births after 41 weeks of gestation, [6][7][8] but European data on these rates are not available. This analysis uses populationlevel data on gestational age to compare rates of births at 42 weeks of gestation or later in European countries; these data were collected as part of the PERISTAT project on perinatal health indicators.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Systematically proposing induction is a long-standing policy in many countries, including France and Canada; 2,4 in 2004, the American College of Obstetricians and Gynecologists updated their guidelines to promote a policy of systematic induction more actively but recommended that women 'with unfavourable cervixes can undergo labour induction or be managed expectantly'. 5 Studies from Australia, Canada, and the USA report recent rates of births after 41 weeks of gestation, [6][7][8] but European data on these rates are not available. This analysis uses populationlevel data on gestational age to compare rates of births at 42 weeks of gestation or later in European countries; these data were collected as part of the PERISTAT project on perinatal health indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Trends of gestational shortening have been reported in other countries [17][18][19][20] . A study carried out in Australia 17 including births from 1990 to 1996 showed a decline in 40 and .…”
Section: Discussionmentioning
confidence: 93%
“…At the clinical setting, programs to reduce post-term pregnancies, better survival of increasingly premature births, increase of fertility treatments and obstetrical procedures such as elective caesarean section or elective induced labor are all factors that contribute to reduce the average duration of gestational age at birth in a population 1,[14][15][16] . The coexistence of many of these factors in current industrialized societies could be the explanation for the shortening of the gestational length identified in some recent studies [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…A trend of shortening duration of pregnancies carried to term has been observed in several countries . Gestational age is an important predictor of the newborns' future health and development.…”
Section: Introductionmentioning
confidence: 99%
“…While this can be interpreted as an artefact, the use of obstetric interventions is not. Studies that tested the relationship between the mode of delivery (spontaneous vs induced onset, vaginal vs CS) and gestational duration found the increasing use of induction and CS as an important substantive explanation for the shortening gestational age …”
Section: Introductionmentioning
confidence: 99%